Challenging the dominance of formalism in accounting education: An analysis of the potential of stewardship in light of the evolution of legal education. (May 2017) - Murphy, Tim; O'Connell, Vincent
Abstract: In this article we draw parallels between law and accounting in order to articulate the concept of "accounting formalism, " which refers to both a theory of accounting practice and a methodology of accounting education. We argue that accounting formalism reigns supreme in contemporary accounting education, and we contrast this with the fate of legal formalism, which, while remaining the dominant mode of legal education, nonetheless declined considerably in influence during the twentieth century. We suggest that the dominance of formalism has resulted in an undue emphasis on the technical aspects of accounting education and a relative pedagogical neglect of the social, critical and ethical dimensions. Drawing on two largely separate discourses in accounting – that which surrounds the role of stewardship/accountability and that which focusses on accounting education – we argue that stewardship/accountability has the capacity to act as the ideal conduit for integrating formalist and anti-formalist perspectives in accounting theory and thereby provide an appropriate and necessary challenge to the dominance of formalism in accounting education. In addition, we propose that stewardship/accountability, as part of the living law (i.e., the moral or customary tradition) of accounting, has the capacity to provide the conceptual foundations for challenging formalism across the inter-related social, critical and ethical dimensions of accounting theory and education. We suggest that such a challenge would bring about multifarious benefits, not only for all those who participate in and thereby constitute the accounting academy, but also for other stakeholders dissatisfied with the trajectory of the current formalist-dominated mode of accounting education.